Syntheses and applications of C-2-symmetric chiral diols - Bhowmick, Kartick C.; Joshi, Navalkishore N. (Tetrahedron-Asymmetry, 2006)
Synthetic procedures for a large variety of C-2-symmetric chiral diols are reviewed. Prominent among these procedures are enantioselective reductions, epoxide-cleavages, dihydroxylation of olefins, and synthetic transformations. Applications of these diols as chiral auxiliaries/ligands for several important reactions are also highlighted. (c) 2006 Elsevier Ltd. All rights reserved.

Stereocontrolled route to the synthesis of (+/-)-3-amino-2,2-dimethyl-1,3-diphenylpropan-1-ol - Patil, M. N.; Bhowmick, Kartick C.; Joshi, Navalkishore N. (Tetrahedron Letters, 2010)
Both the diastereomers of (+/-)-3-amino-2,2-dimethyl-1,3-diphenylpropan-1-ol were synthesized starting from a common intermediate, namely,B-hydroxy, oxime 6. Diastereoselective reduction with NaBH(4)/TiCl(4) and H(2)-Pd/C provided syn- and anti-isomers, respectively. Good overall yield and selectivity were realized using a simple protocol. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-Aminoalcohol; Aldol-Tishchenko reaction; beta-Hydroxy oxime; Diastereoslective reduction

Smallest organocatalyst in highly enantioselective direct aldol reaction in wet solvent-free conditions - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (RSC Advances, 2014)
The catalytic efficacy of the smallest organocatalyst, L-proline hydrazide, prepared from a cheaply available natural amino acid, such as L-proline, was studied for the direct asymmetric aldol reaction of various ketones with aromatic aldehydes at room temperature in the presence of several acid additives. A loading of 10 mol% of catalyst 1 and p-toluenesulphonic acid as an additive was employed in this reaction, and good yields (up to 99%) with high anti/syn diastereoselectivities (up to 95 : 5) and enantioselectivities (up to >99.9%) were achieved in aqueous media.